2014
DOI: 10.1007/s11033-014-3140-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNAs and pathologic response to preoperative chemotherapy in triple negative breast cancer: preliminary report

Abstract: Triple negative breast cancer (TNBC) has caught the attention of oncologists worldwide because of poor prognosis and paucity of targeted therapies. Gene pathways have been widely studied, but less is known about epigenetic factors such as microRNAs (miRNAs) and their role in tailoring an individual systemic and surgical approach for breast cancer patients. The aim of the study was to examine selected miRNAs in TNBC core biopsies sampled before preoperative chemotherapy and the subsequent pathologic response in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 18 publications
4
36
0
1
Order By: Relevance
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Overexpression of miR-200c in TNBC cells (MDA-MB-231 cell line) resulted in loss of the elongated shape associated with a motile, mesenchymal phenotype and acquisition of the epithelial-like morphology. Downregulation of miR-200b was found crucial in increase of EMT in TNBC cells by targeting ZEB1/2 and suppressing PKCα (Kolacinska et al 2014; Humphries et al 2014; Rhodes et al 2015). Loss of the actin-based structure was orchestrated by miR-200c, which directly targeted actin regulatory proteins, FHOD1 and PPM1F, in a ZEB1/2-independent manner and led to the inhibition of migration and invasion of the cells (Jurmeister et al 2012).…”
Section: Micrornasmentioning
confidence: 99%
“…The predictive and prognostic value of miRNAs has been investigated in breast cancer . In a small study (n = 11), Kolacinska et al found higher expression of miR‐200b‐3p/miR‐190a along with lower expression of miR‐512‐5p in breast cancer tissue before chemotherapy correlated with a better pathologic response to NCT. Wang et al proposed circulating miR‐125b as a marker predicting chemo‐resistance in breast cancer.…”
Section: Introductionmentioning
confidence: 99%